Migrants: Where do they come from?. Issue 1 (February 2014) - Hill, Timothy Martyn; Smith, Alan
<x xml:space="preserve">Abstract</x> Where do migrants come from, and where do they go? Politicians make claim and counter‐claim, but what is significant immigration, and what is less significant, and how do you map it so that people can tell which is which? Timothy Martyn Hill and Alan Smith needed to do just that.